Letters to the Editor - TART, CHARLES T.; ALVARADO, CARLOS S. (Journal of Scientific Exploration, 2010)
On the Reality of Other Worlds Charles - T. Tart Historical Examples of the Use of Newspapers as ESP Targets - Carlos S. Alvarado